Choice and autonomy in everyday life for eight adults with physical disabilities - Collins, Bethan (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Occupational Therapy, 2009)
This research seeks to explore the daily life experience of eight adults with significant physical disability, with a particular focus on their experience and perceptions of autonomy and choice in everyday life. It involves detailed description of the lives and lifestyles of each of the individuals, their life history and their experiences and views of autonomy and choice. Also explored is the literature within psychology, rehabilitation, occupational therapy and disability studies, concerned with autonomy, choice and other relevant areas.
Keywords: Occupational Therapy, Ph.D.; Ph.D. Trinity College Dublin